DAMPAK PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 TERHADAP PERUBAHAN MENTAL REMAJA DI SMPN 1 BLITAR - Manda, Tyithania Agustria; Anjaswarni, Tri; Wiyono, Joko; Bahari, Kissa (Poltekkes Kemenkes Malang, 2024)
The COVID-19 pandemic in Indonesia occurred in March 2020 and is increasing throughout Indonesia. Based on this, the Ministry of Education and Culture of the Republic of Indonesia held online-based learning in the context of preventing the spread of COVID-19. Online learning from home, causes many students to complain, so it is possible to cause problems with mental changes in adolescents, such as depression, anxiety and stress. The purpose of this study was to analyze the impact of online learning during the COVID-19 pandemic on the mental changes of adolescents at SMPN 1 Blitar. This type of research is correlational with a cross sectional approach with a sample of 76 respondents at SMPN 1 Blitar using proportional random sampling technique and then analyzed using the Pearson Product Moment test. Data collection using the DASS42 questionnaire. The results showed that the impact of online learning during the pandemic was 38.2% depression, 36.8% anxiety and 38.2% stress. Based on the results of the analysis, it is known that there is a significant relationship between online learning during the pandemic and the occurrence of depression in students with Pv = 0.001, anxiety with Pv = 0.000 and stress with Pv = 0.006. Therefore, researchers suggest that students should motivate students to generate interest in learning and must foster positive thinking in students so that their physical and mental health can be maintained properly.